Pregunta
\[ f(x) = 3x + 4 \quad g(x) = 2x - 3 \] \[ \text{Find: } f \circ g(x) \]
Ask by Peterson Cook. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( f \circ g(x) = 6x - 5 \)
Solución
To find the composition \( f \circ g(x) \), we need to evaluate \( f \) at \( g(x) \). Here's a step-by-step breakdown:
Given:
\[
f(x) = 3x + 4 \quad \text{and} \quad g(x) = 2x - 3
\]
**Step 1:** Write the composition \( f \circ g(x) \) as \( f(g(x)) \).
\[
f \circ g(x) = f(g(x))
\]
**Step 2:** Substitute \( g(x) \) into \( f(x) \).
\[
f(g(x)) = f(2x - 3)
\]
**Step 3:** Replace \( x \) in \( f(x) \) with \( 2x - 3 \).
\[
f(2x - 3) = 3(2x - 3) + 4
\]
**Step 4:** Distribute and simplify.
\[
3(2x - 3) + 4 = 6x - 9 + 4 = 6x - 5
\]
**Final Answer:**
\[
f \circ g(x) = 6x - 5
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Mind Expander
To find \( f \circ g(x) \), we need to substitute \( g(x) \) into \( f(x) \). 1. We first find \( g(x) \): \[ g(x) = 2x - 3 \] 2. Then, we substitute \( g(x) \) into \( f(x) \): \[ f(g(x)) = f(2x - 3) = 3(2x - 3) + 4 \] 3. Now, simplify it: \[ = 6x - 9 + 4 = 6x - 5 \] Thus, the composition \( f \circ g(x) \) is: \[ f \circ g(x) = 6x - 5 \]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium